2011
DOI: 10.1089/neu.2010.1662
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Injury to Medium Spiny Neurons and White Matter in the Mouse Striatum after Prolonged Transient Global Cerebral Ischemia

Abstract: A reproducible transient global cerebral ischemia (tGCI) mouse model has not been fully established. Although striatal neurons and white matter are recognized to be vulnerable to ischemia, their injury after tGCI in mice has not been elucidated. The purpose of this study was to evaluate injuries to striatal neurons and white matter after tGCI in C57BL/6 mice, and to develop a reproducible tGCI model. Male C57BL/6 mice were subjected to tGCI by bilateral common carotid artery occlusion (BCCAO). Mice whose corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…The survival rate of the 15-minute PCA-ischemic mice that showed CA1 neuronal death was 95.8%, and all mice that survived 1 day after PCA ischemia survived 7 days after PCA ischemia (longer survival times were not examined). In contrast, the survival rates in previous BCCAO models were low (75% after a 15-minute BCCAO in CD1 mice 29 and 81.6% after a 22-minute BCCAO in C57BL/6 mice (however, more than 50% of the surviving mice suffered from severe akinesia 28 ). Even with the strict criteria for rCBF, only ≤ 50% of the mice were found to have bilateral CA1 injury.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The survival rate of the 15-minute PCA-ischemic mice that showed CA1 neuronal death was 95.8%, and all mice that survived 1 day after PCA ischemia survived 7 days after PCA ischemia (longer survival times were not examined). In contrast, the survival rates in previous BCCAO models were low (75% after a 15-minute BCCAO in CD1 mice 29 and 81.6% after a 22-minute BCCAO in C57BL/6 mice (however, more than 50% of the surviving mice suffered from severe akinesia 28 ). Even with the strict criteria for rCBF, only ≤ 50% of the mice were found to have bilateral CA1 injury.…”
Section: Discussionmentioning
confidence: 83%
“…These histological changes resembled conventional global cerebral ischemia in mice. 13,20,25,27,28 Many researchers have attempted to produce a mouse model of global cerebral ischemia to ensure consistent CA1 injury. The simplest and most widely used model is the bilateral CCA occlusion (BCCAO) model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier study, we found that ischemic neuronal injury is consistently induced after prolonged transient global ischemia. 24 In addition to ischemic vulnerability, the striatum is reported to be one of the selected areas where severe neuronal loss is observed in PARL knockout and HtrA2 mutant or knockout mice. 11,17,18 Accordingly, the roles of PARL and HtrA2 signaling in the other lesions are obscure.…”
Section: Discussionmentioning
confidence: 99%